2015
DOI: 10.1517/14740338.2015.1032242
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intravenous thrombolysis for acute ischemic stroke in specific conditions

Abstract: The present narrative review summarizing 20 years of clinical experience with IVT for AIS highlights that many of the current guidelines and protocols should be adjusted to accommodate recent data from registries and real-world experience underscoring the safety of IVT in numerous conditions of AIS that were originally considered as relative or absolute contraindications for administration of IV-tPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 195 publications
0
29
0
1
Order By: Relevance
“…In particular, many of the criteria used in clinical trials may no longer be relevant given that the drug was first approved over 20 years ago [20-22]. Mounting evidence from pooled analyses, observational studies and clinical trials, some studying an extended time window of 4.5 h and practices less adherent with standard criteria, suggests that rtPA can be delivered safely to patients previously deemed ineligible [22-31]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, many of the criteria used in clinical trials may no longer be relevant given that the drug was first approved over 20 years ago [20-22]. Mounting evidence from pooled analyses, observational studies and clinical trials, some studying an extended time window of 4.5 h and practices less adherent with standard criteria, suggests that rtPA can be delivered safely to patients previously deemed ineligible [22-31]. …”
Section: Introductionmentioning
confidence: 99%
“…30 In cases with intracranial extension, a high rate of associated subarachnoid hemorrhage has been observed, making dual-antiplatelet therapy a better choice for our patient over intravenous fibrinolytics or anticoagulation. 9,42 In critical cases, endovascular intervention is highly favored over open surgical repair due to its exceedingly lower perioperative stroke risk (0.02% vs 10%) and mortality rate (nearly 0% vs 2%). 33,45 Our patient's critical stenoses made her a candidate for acute endovascular intervention especially since she, a young, active woman, was experiencing recurring dominant-hemisphere symptoms at rest (despite collateral circulation), putting her at high risk for future hypoperfusion and possible stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial hemorrhage and recurrent infarction in patients with carotid dissection were found to occur approximately as frequently as in patients without carotid dissection [ 3 ]. The Safe Implementation of Thrombolysis in Stroke-Monitoring Study also reported that the occurrence of adverse effects was similar with or without intravenous thrombolysis in patients with cerebral infarction caused by carotid or vertebral dissection [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was reported that thrombolysis could cause hemopericardium or cardiac tamponade by aortic rupture [ 5 ]. Thrombolysis could reduce the patient’s possibility of survival by leading to the postponement of an emergency operation to treat a Stanford Type A aortic dissection [ 4 ].…”
Section: Discussionmentioning
confidence: 99%